2017
DOI: 10.1038/srep43934
|View full text |Cite
|
Sign up to set email alerts
|

A biomimetic gelatin-based platform elicits a pro-differentiation effect on podocytes through mechanotransduction

Abstract: Using a gelatin microbial transglutaminase (gelatin-mTG) cell culture platform tuned to exhibit stiffness spanning that of healthy and diseased glomeruli, we demonstrate that kidney podocytes show marked stiffness sensitivity. Podocyte-specific markers that are critical in the formation of the renal filtration barrier are found to be regulated in association with stiffness-mediated cellular behaviors. While podocytes typically de-differentiate in culture and show diminished physiological function in nephropath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 84 publications
5
36
0
1
Order By: Relevance
“…When podocytes were cultured in substrate with stiffness similar to that of in vivo glomeruli tissues (2-5 kPa), they exhibited phenotypes indicative of cellular differentiation. 86 This supports the theory that in general, the physical and mechanical properties of gelatin substrate whether it is because of the increased ECM concentration or the increase in the degree of crosslinking affects cell adhesion, proliferation, migration, and differentiation.…”
Section: Gelatin-based 2d Biomaterials For Cell and Tissue Culturessupporting
confidence: 79%
“…When podocytes were cultured in substrate with stiffness similar to that of in vivo glomeruli tissues (2-5 kPa), they exhibited phenotypes indicative of cellular differentiation. 86 This supports the theory that in general, the physical and mechanical properties of gelatin substrate whether it is because of the increased ECM concentration or the increase in the degree of crosslinking affects cell adhesion, proliferation, migration, and differentiation.…”
Section: Gelatin-based 2d Biomaterials For Cell and Tissue Culturessupporting
confidence: 79%
“…adhesion, and potentially, altered gene expression patterns (dedifferentiation). 5,6 We show that increasing numbers of biophysically defective podocytes (Tg26) causes progressive loss of three-dimensional collagen gel contraction, a simple model of the mechanical role of podocytes in a glomerulus (Figure 7). Defective structure and reduced adhesion of these cells would increase their susceptibility to detachment and loss in response to shear force.…”
Section: Discussionmentioning
confidence: 88%
“…culturing podocytes on soft matrix (,2 kPa) causes a reduction in mRNAs coding for filamin A, nonmuscle myosin IIa, WT-1 protein expression, and expression of other differentiation markers. 5,6,26,29 Inhibition of integrin and cadherin function reduced glomerular E, indicating that cell matrix and cell-cell adhesion both contribute to a normal glomerular mechanical environment. 5 The reduced E value of an individual injured podocyte would not only provide inadequate structural support to a capillary at that location but could also reduce the ability of normal neighboring podocytes to Figure 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al [49] and, more recently, Abdallah et al [31] studied the effects of substrate mechanical characteristics on podocytes. Hu et al reported a pro-differentiation and maturation effect of gelatin substrates with Young's modulus near that of healthy glomeruli (in the 2-5 kPa range) and suggested that Src-mediated activation of RacGAPs may be responsible for the mechanoresponse of podocytes [31].…”
Section: Discussionmentioning
confidence: 99%